METAMORFOSA DALAM RELASI YAN’UR-MANG’OHOI - Refo, Ignasius SS. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2014)
Using filed study, I chose Lumefar village, a small village in the south of Kei Kecil Island. For the society of Lumefar, the most important relationship is the relationship by marriage (yan'ur-mang'ohoi). This relationship unites two Houses; and each House has several yan'ur- mang'ohoi relations with other Houses. But the ideal model of this relation has changed. In this paper, I intend to explain this metamorphosis. The society of Lumefar apparently has moved from the elementary structure of kinship to the complex structure of kinship.